THE EFFECT HEALTH EDUCATION ON PERSONAL HYGIENE KNOWLEDGE DURING MENSTRUAL IN STUDENTS AT SDN 01 V KOTO TIMUR - ZAYANI, NOFRI; YOLANDA, YOSI (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2025)
Reproductive health is a long-term asset that determines the success of having children. Maintaining reproductive organs in the form of personal hygiene actions is key to reproductive health, especially during menstruation. The lack of knowledge of a teenager in carrying out personal hygiene actions for external reproductive organs can trigger various diseases. The purpose of this study was to determine the effect of reproductive health education about personal hygiene during menstruation on the level of knowledge of female students at SDN 01 V Koto Timur. This study was quantitative with a pre-experimental design with a one group pretest posttest approach. The study was conducted on November 26, 2024 at SDN 01 V Koto Timur. The study population was all students of SDN 01 V Koto Timur who had experienced menstruation. The research sample was students who had experienced menstruation with a total sampling technique so that a sample of 35 people was obtained. The instrument used in the study was a knowledge questionnaire containing 15 question items with a Gutman scale. Data analysis used a paired t-test at the α level = 5%. The results of the study showed that the majority of students had a low level of knowledge, namely 25 people (71.43%) regarding personal hygiene during menstruation before being given reproductive health education. However, the majority of students had good knowledge of personal hygiene, namely 30 people (85.71%) after being given reproductive health education. The results of the paired t-test showed p-value = 0.002 <α = 0.05. It can be concluded that there is an effect of providing reproductive health education on the level of knowledge of personal hygiene during menstruation in students of SDN 01 V Koto Timur. Suggestion, this study is expected to be a reference for schools to provide education about personal hygiene periodically to students who are menstruating to avoid genital infections.